Household- and community-level factors of zero vegetable or fruit consumption among children aged 6–23 months in East Africa - Endawkie, Abel; Gedefie, Alemu; Muche, Amare; Mohammed, Anissa; Ayres, Aznamariam; Melak, Dagnachew; Abeje, Eyob Tilahun; Bayou, Fekade Demeke; Belege Getaneh, Fekadeselassie; Asmare, Lakew (Frontiers in Nutrition, 2024)
The World Health Organization recommends that children aged 6 to 23 months should consume a diversified diet including fruits and vegetables during each meal. However, low consumption of fruits and vegetables contributes to 2.8% of child deaths globally. Moreover, according to our literature search, there is limited research showing the factors determining zero vegetable and/or fruit consumption among children aged 6-23 months in East Africa. Therefore, this study aims to investigate the household and community-level factors determining zero vegetable and/or fruit consumption among children aged 6-23 months in East Africa.Method: Cross-sectional secondary data were analyzed using the recent rounds of demographic and health survey data in East Africa from 2015 to 2023 among 113,279 weighted samples of children aged 6-23 months. Multilevel mixed-effect analysis was used. The intra-cluster correction coefficient, the median odds ratio, and the proportional change variance were used to measure the random variation between the clusters. Adjusted odds ratio with 95% confidence interval was reported and variables at p-value less than 0.05 were statistically significant.The overall prevalence of zero vegetable and/or fruit consumption among 6-23 month children in East Africa was 52.3% with the highest percentage in Ethiopia (85.9%). Maternal educational status, number of household members, short birth interval, multiple births, sex of the household head, household wealth index, community-level maternal literacy, community-level wealth index, and countries were associated with zero vegetable and/ or fruit consumption.The overall prevalence of zero vegetable and/or fruit consumption among 6-23 month children in East Africa was high and it was highest in Ethiopia. Maternal educational status, short birth interval, multiple births, number of household members, sex of the household head, household wealth index, community-level maternal literacy, community-level wealth index, and country of residence were factors of zero vegetable and/or fruit consumption.Overlooking zero vegetable and/ or fruit consumption among children is a serious mistake. Therefore, it is recommended that efforts should be geared toward improving individual and community-level maternal literacy. Particularly various nutrition and public health organizations should support poor communities to achieve diet diversity for infants and young children.